Flood Frequency Analysis For Sarawak Using Weibull, Gringorten And L-Moments Formula - Onni S., Selaman; Salim, Said; Putuhena, F.J. (The Institution of Engineers, Malaysia, 2007)
The objective of this study is to determine the magnitude and frequency of floods for Sarawak using Gumbel distribution. Nineteen stations were selected for the study based on the criteria stated in Hydrological Procedure No. 4 (HP4). The probability plot and flood-frequency curves by Gumbel distribution of each individual station are prepared using three different plotting position formulas (i.e. Weibull, Gringorten and L-Moments). From the results and analysis of each individual station, Gumbel distribution based on L-Moments always give the least ratio of peak discharge of T year’s recurrence interval over mean annual flood (QT/MAF) but at some stations, it gives unreasonable return period (T) and reduced variate (y) range. The appropriateness of L-moments with Gumbel distribution had some limitation. It is only good for small samples data. If compared between Gumbel distribution by Weibull formula and Gumbel distribution by Gringorten formula, the latter is better because it gives the least ratio (which is in agreement with the literature). Therefore, it could be concluded that for some stations, LMoments method is the best, but since L-Moments method had some limitations, Gringorten formula is still the best plotting position method to be applied with Gumbel distribution.